Earth Science - Tarbuck, Edward J. (Pearson Education, 2015)
Ideal for undergraduates with little or no science background, this text provides a student-friendly overview of our physical environment that offers balanced, up-to-date coverage of geology, oceanography, astronomy, and meteorology. The authors' texts have always been recognized for their readability, currency, dynamic art program, delivery of basic principles and instructor flexibility. The Fourteenth Edition incorporates a new active learning approach, a fully updated and mobile visual program, and MasteringGeology, the most complete, easy-to-use, engaging tutorial and assessment tool available. This program will provide an interactive and engaging learning experience for your students. Here's how: Personalize learning with MasteringGeology): MasteringGeology provides students with engaging and interactive experiences that coach them through introductory physical geography with specific wrong-answer feedback, hints, and a wide variety of educationally effective content. Teach with an active learning path: Chapters have been broken up into small manageable sections that help students actively analyze information, assess their progress and think about Earth science. Use art that teaches. Each chapter contains 5-7 SmartFigures. SmartFigures are illustrations that use Quick Response (QR) codes to link students to lecture-style videos. Also found in each chapter and accessed by QR codes are Mobile Field Trips, where students virtually accompany Michael Collier on adventures to explore different landscapes.